2008
DOI: 10.1063/1.2830719
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of disordered double-perovskite Ca2−xLaxFeIrO6

Abstract: In this work we have synthesized polycrystalline samples for the series of double-perovskite Ca2−xLaxFeIrO6. Their structural and magnetic properties were investigated using experiments of magnetic susceptibility and x-ray powder diffraction. The Ca2−xLaxFeIrO6 compounds form in a monoclinic structure, space group P21∕n, with the presence of significant Fe∕Ir cationic disorder. Interestingly, our results indicate a change in the nature of the microscopic magnetic interaction induced by La doping, where the sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 11 publications
1
9
1
Order By: Relevance
“…1. As expected, it is a single-phase DP belonging to monoclinic P 2 1 /n space group, since both La 2−x Ca x CoIrO 6 and La 2−x Ca x FeIrO 6 series form in this same space group [15,20]. The Rietveld refinement indicates ∼10% of antisite disorder (ASD) at Co/Fe and Ir sites.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…1. As expected, it is a single-phase DP belonging to monoclinic P 2 1 /n space group, since both La 2−x Ca x CoIrO 6 and La 2−x Ca x FeIrO 6 series form in this same space group [15,20]. The Rietveld refinement indicates ∼10% of antisite disorder (ASD) at Co/Fe and Ir sites.…”
Section: Resultssupporting
confidence: 70%
“…Further studies of this material revealed magnetodielectric effect together with re-entrant spin-glass behavior at low-T [13], whereas Ca 2+ to La 3+ partial substitution leads to compensation temperatures and spontaneous exchange bias effect in La 1.5 Ca 0.5 CoIrO 6 (LCCIO) [14]. For the case of Fe-and Ir-based DPs, the Ca 2+ to La 3+ partial substitution in La 2−x Ca x FeIrO 6 induces interesting changes in the nature of the microscopic magnetic interactions between the TM ions, where the system evolves from antiferromagnetic (AFM) in the x = 0 and 2.0 extremities of the series to FM-like in the x ∼ 1.0 intermediate region, this being ascribed to changes in Ir formal valence [15].…”
Section: Introductionmentioning
confidence: 99%
“…Presence of superlattice reflection at around 2θ = 20 The EXAFS data analysis provide finest details about the local coordination geometry and local chemical order (the antisite defects) which are complementary to structural information obtained from XRD analysis (Rietveld refinement) which only probes long range coherent structural features. The local antisite disorder in the double perovskite structure often largely influences the magnetic response [26][27][28] . Therefore, to confirm the local coordination around (IrO 6 ) and also the chemical order (antisite defects) at both the A-and B-sites, the Ir L 3 -edge EXAFS data (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, it was only found in La 2 FeIrO 6 [28]. In La 2 FeIrO 6 , the fully occupied u level and fully occupied e level of Ir 3+ (5d 6 ) lead to a nonmagnetic ground state (J ef f = 0), thus there are only superexchange AFM coupling between Fe 3+ cations [29]. To achieve the combination of +1/+5, one way is to place alkali metal cations on the B site.…”
Section: Discussionmentioning
confidence: 96%